2009
DOI: 10.1093/arclin/acp012
|View full text |Cite
|
Sign up to set email alerts
|

The Comprehensive Affect Testing System-Abbreviated: Effects of Age on Performance

Abstract: Deficits in the ability to recognize emotions in others have been noted in a wide variety of disorders, ranging from the psychiatric to the neurologic. Emotions are vital to social interactions, yet there are currently few standardized neuropsychological measures in common use to assess emotion perception abilities. This study examined the effects of age on performance of the Comprehensive Affect Testing System, a new assessment battery designed to measure perception of emotion via facial affect, prosody, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
3
15
0
Order By: Relevance
“…In accordance with prior studies, older age was associated with a particular decline in performance on prosody (25), whereas better attention performance correlated with more accurate general emotion, facial affect, and prosody recognition and better working memory with better prosody recognition (45). Furthermore, concordant with a previous study applying the MSCEIT (20) and the CATS-A, respectively (25), in our study, higher IQ scores were associated with better general and prosodic emotion recognition. Moreover, corroborating our finding from the first assessment of the present study sample (23), demonstrating that a smaller social network correlated with deficient emotional empathy, here, a larger total social network size was associated with better general emotion and prosody recognition.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…In accordance with prior studies, older age was associated with a particular decline in performance on prosody (25), whereas better attention performance correlated with more accurate general emotion, facial affect, and prosody recognition and better working memory with better prosody recognition (45). Furthermore, concordant with a previous study applying the MSCEIT (20) and the CATS-A, respectively (25), in our study, higher IQ scores were associated with better general and prosodic emotion recognition. Moreover, corroborating our finding from the first assessment of the present study sample (23), demonstrating that a smaller social network correlated with deficient emotional empathy, here, a larger total social network size was associated with better general emotion and prosody recognition.…”
Section: Discussionsupporting
confidence: 88%
“…Strikingly similar results with regard to prosodic processing have been reported for schizophrenia patients and it has been suggested that due to their specific nature, the deficits may occur further downstream at the level of complex emotion comprehension (45). Moreover, results derived from human neuroimaging and brain lesion studies (25, 46) have revealed that particularly right inferior frontal and striatal regions are implicated in prosodic processing. Therefore, the notion that drug-induced neuroadaptations in frontostriatal regions in CU (6, 811, 13) may contribute to deficient prosody processing appears plausible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, validated prosodic stimulipseudowords or pseudoutterances-are not yet available in Italian. The few studies addressing the emotional processing of prosodic stimuli have generally used prosodic subtests of emotion recognition batteries (such as the Comprehensive Affect Testing System; Schaffer, Wisniewski, Dahdah, & Froming, 2009), in which actors produce sentences with different emotional tones (Ariatti, Benuzzi, & Nichelli, 2008;Castagna et al, 2013). Although most of the above-mentioned sets of stimuli covered a wide range of basic emotions, we chose to focus on angry, happy, and neutral emotional prosody.…”
Section: Introductionmentioning
confidence: 99%